2021
DOI: 10.3390/jcm10040810
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation: The New Challenges of Cardiac Rehabilitation

Abstract: Transcatheter aortic valve implantation (TAVI) is an increasingly widespread percutaneous intervention of aortic valve replacement (AVR). The target population for TAVI is mainly composed of elderly, frail patients with severe aortic stenosis (AS), multiple comorbidities, and high perioperative mortality risk for surgical AVR (sAVR). These vulnerable patients could benefit from cardiac rehabilitation (CR) programs after percutaneous intervention. To date, no major guidelines currently recommend CR after TAVI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…In this context, CTR may be a cost-effective alternative to add-on interventions [ 18 ]. However, it is also important to bear in mind that patients who undergo TAVI are often octogenarians and frail [ 6 , 51 ], which may have influenced patient withdrawal in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, CTR may be a cost-effective alternative to add-on interventions [ 18 ]. However, it is also important to bear in mind that patients who undergo TAVI are often octogenarians and frail [ 6 , 51 ], which may have influenced patient withdrawal in our study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no major guidelines recommend cardiac rehabilitation (CR) after TAVI [ 5 ], although emerging evidence suggests that CR is safe and has the potential to reduce mortality and improve exercise capacity and quality of life [ 6 - 9 ]. Participation in CR soon after TAVI may be of particular importance as sedentary behavior in this often frail population with multiple comorbidities is related to a higher risk of mortality and functional decline 1 year after the procedure [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of resistance exercise training, aerobic training, sufficient protein intake and good diet quality has shown to effectively increase muscle strength and physical performance [ 57–60 ]. However, due to frailty, old age and symptoms of severe aortic stenosis, currently available interventions do not immediately apply to the TAVI population [ 61 ]. Creative solutions are warranted to increase feasibility, adherence and motivation in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Creative solutions are warranted to increase feasibility, adherence and motivation in this patient group. These might include technology-supported home-based interventions, functional training with a physiotherapist or involvement of a training buddy [ 61 , 62 ]. Furthermore, it is currently unknown if improved muscle strength and physical performance also lead to better long-term outcomes in this older and frailer patient population [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…An aspect of patients not willing to participate in inpatient CR should be mentioned. Patients who decline CR are different from those willing to participate, not in clinical characteristics but in behavioral or socioeconomical aspects, which may play an important role [ 20 ]. In our study following reasons for declining CR were observed: social factors, the presence of a caregiver at home, the program’s distance from home, and family problems.…”
Section: Discussionmentioning
confidence: 99%